The Correlation between Reading Self-Efficacy and Reading Comprehension - Dona Rahma Fitri E.; Dedi Sofyan; Fernandita Gusweni Jayanti (Journal of English Education and Teaching, 2019)
AbstractThe purpose of this research was to find out the correlation between reading self-efficacy and reading comprehension. The research applied correlational study which used quantitative design. The sample was 273 of twelfth grade students of science class at SMAN 5 Bengkulu. The data were collected by using two instruments: (1) the reading self-efficacy questionnaire which was used to measure the students’ reading self-efficacy and (2) reading comprehension test which was used to know the students’ reading comprehension. The correlation between the two variables was calculated by using Pearson Product Moment in SPSS 15. The result shows that there is a significant correlation between reading self-efficacy and reading comprehension. The score of significance level is < 0.05 (0.000 < 0.05) which means that H1 was accepted and H0 was rejected. So, it can be inferred that the higher the reading self-efficacy, the higher the reading comprehension. Keywords: Reading Comprehension; Self-Efficacy